Membongkar Mitos Korban Pedofilia Studi Semiotika Roland Barthes Pada Video Klip Avicii “For a Better Day” - Fadillah, Nazmiah Nur; Nurliah, Nurliah; Kristian, Dony (Jurnal sosial dan sains, 2025)
The increasingly rapid technology gives birth to various digital advancements in the field of entertainment. A music video is a combination of song and video whose main purpose is not only merely entertainment, but also as a medium of promotion and campaign. Many musicians often insert messages about certain issues in their music videos, one of them is Avicii. The music video titled “For A Better Day” by Avicii contains the issue of pedophilia which is displayed explicitly. This research aims to reveal the myth of pedophilia victims represented in the music video by using Roland Barthes’ semiotics theory and Stuart Hall’s representation theory. The research uses a qualitative semiotic approach as the main foundation of observation. The focus of the research is how pedophiles are represented based on several indicators which then continue to the stigma and myths about victims of pedophilia. This research contains two types of data in its process, namely primary data and secondary data. The primary data are information obtained based on observation and analysis of the “For A Better Day” music video, while the secondary data are based on various literature studies such as books, journals, articles, theses, and the internet related to pedophiles, victims of pedophilia, as well as other relevant data connected to the research object.